Salt water and silicon application on growth, chloroplastid pigments, chlorophyll fluorescence and beet production - Melo-Filho, José Sebastião de; Silva, Toshik Iarley da; Gonçalves, Anderson Carlos de Melo; Sousa, Leonardo Vieira de; Véras, Mario Leno Martins; Dias, Thiago Jardelino (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
In recent years, the use of saline water in agriculture has become an alternative mainly because of water scarcity. However, plants do not tolerate high salt contents; so, the use of salt stress attenuators could enable saline water usage in agriculture. This study aimed to assess the effect of saline water and silicon applications on growth, chloroplastid pigments, chlorophyll fluorescence a and beet production. The experiment was conducted with complete randomized blocks in a 5 x 5 combined factorial arrangement according to the Central Composite of Box experiment matrix for the electrical conductivity in the irrigation water (ECw) and silicon doses (Si), with minimum (- α) and maximum (α) values from 0.5 to 6.0 dS m-1 and from 0.00 to 18.16 mL L-1, totaling nine treatments, with four replicates and three plants per plot. The irrigation water ECw increase reduced growth and beet production, but the chlorophyll contents, biomass and fluorescence production were not affected by salinity. Silicon applications via the soil increased growth and chlorophyll fluorescence a but did not reduce the harmful effect of the salt stress. The irrigation water ECw above 0.50 dS m-1 negatively affected the beet crop. The silicon dose of 9.08 mL L-1 is the most recommended application.